PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM SYARIAH: Studi Kasus PT. Aneka Tambang Persero Tbk Tahun 2013-2017 - Firman Setiawan; Desi Ismi Rojasari (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
Sharia share prices (including conventional shares) always fluctuate due to the interaction of demand and supply of shares in the capital market. Rising levels of demand for shares will trigger a rise in stock prices, and vice versa. However, aside from supply and demand factors, it turns out that there are other factors that are also identified as being capable and potentially affecting stock prices, particularly Shariah share prices, namely Return On Assets (ROA), Return On Equity (ROE), and market ratios namely Earning Per Share (EPS). So to prove whether the financial ratios really have an influence on sharia stock prices, the authors conducted a quantitative analysis with ROA, ROE and EPS as X variables and Shariah stock prices as Y variables. The data used in this test / analysis are Return On Assets (ROA), Return On Equity (ROE) data, Earning Per Share (EPS) and Syariah stock prices from PT. Aneka Tambang Persero Tbk 2013-2017. From the analysis that has been done, it is known that partially ROA has no effect on the Shariah share price caused by the lack of companies in earning profit, ROE has no effect on the Sharia share price caused by the lack of net profit from their own capital and the lack of business sales profits, and EPS positive effect on sharia stock prices. Whereas simultaneously, ROA, ROE and EPS have a positive influence on the Shariah stock price.